BATIK GUMELEM BANJARNEGARA SEBAGAI PEMBENTUK IDENTIFIKASI MEREK KONSUMEN - Fitroh Adhilla; Aftoni Sutanto; Agus Siswanto (Universitas Ahmad Dahlan, 2021)
Banjarnegara as one of the batik producing centers in the Indonesia, namely in the Susukan District, which borders the Banyumas area. However, Batik Gumelem is not as famous as Batik Pekalongan, Batik Solo, or Batik Banyumas. The aim of this research is to analyze the Â effect of social identity to positif words of mouth that mediated of consumer brand identification. This research uses a quantitative approach with a survey method. Primary data were obtained through distributing questionnaires to 185 respondents who knew about Batik Gumelem Banjarnegara. Validity testing uses confirmatory factor analysis and all items have factor loading above 0,6. Reliability testing uses cronbachâ€™s alpha and all variables have cronbachâ€™s alpha above 0,6. The data analysis method uses regression with mediating variable. The results showed that social identity has a positive effect on positive word of mouth, social identity has a positive effect on consumer brand identification, and consumer brand identification has a positive effect on positive word of mouth. Consumer brand identification as role as mediating variable. This shows that Batik Gumelem is perceived to have the power to be able to create an identity for consumers and lead to behavior to disseminate information about Batik Gumelem to others.